Molecular characterization on outer membrane proteins of Shigella flexneri as vaccine candidates - Kazi, Ada Yousef (2018)
In the developing world, bacillary dysentery is one of the most common communicable diarrheal infection. Approximately every year there are approximately 165 million cases of shigellosis that is reported worldwide. Treatment of shigellosis include oral rehydration and the use of antibiotics. However due to uncontrolled use and distribution of antibiotics, has led to the emergence of resistant strains. Shigella is once organism that has shown multiple drug resistance (MDR) to most of the drugs that have been used against it. With rapid increase in resistant strain the best way to combat this infection is by identifying and developing new immunogenic proteins that can be used to develop suitable vaccines. In this study, six immunogenic outer membrane proteins that could be used as potential vaccine candidates in the future were identified using immunoinformatics approach. From these six immunogenic proteins, two full length proteins were selected and expressed as recombinant His-tagged proteins. A chimeric protein that was then engineered by combining partial fragment of these two full length proteins. The expression of these proteins were carried out using BL21 (DE3) bacterial system. Overall, evaluation of these regions for encoding proteins with immunological reactivity can lead to the identification of additional antigens of Shigella which are useful as new vaccines and reagents for specific diagnosis of shigellosis.